An Environment-friendly Synthesis of Piperonal Chalcones and Their Cytotoxic and Antioxidant Evaluation - Dev, Sanal; Thomas Parambi, Della G.; Baby, Bency; Mathew, Githa Elizabeth; Omnia Magdy, Hendawy; Joy, Monu; Sudev, Shine; Mathew, Bijo (Letters in Drug Design & Discovery, 2020)
Background: Grindstone technique has been widely used as an efficient, consistent, more environmentally benign, solvent-free protocol for the preparation of many compounds with higher atom economy. Methods: A series of fourteen piperonal chalcone compounds were synthesized by this method and characterized by physical and spectral data (FT-IR, 1H NMR, Mass and elemental analysis). All chalcones were evaluated for their cytotoxic action against the cancer cell lines, MCF-7 and HepG2. One 2-pyridyl-substituted compound 14 with IC50 values 17.4±0.2 towards MCF-7 and 15.4±0.6μmol L-1 towards HepG2 cells. Results: The results demonstrated that the cytotoxic activity of 2-pyridyl-substituted compound shown higher activity as compared with the standard cisplatin towards HepG2 cells. Conclusion: Compound 14 showed good antioxidant activities in the DPPH test and H2O2 assay (IC50 = 17.23± 33/μg/mL and 20.17± 0.33μg/mL) when compared with the standard ascorbic acid (IC50=μg/mL 18.26 ± 0.22and 21.66± 1.06 μg/mL).
Keywords: Grindstone chemistry